Sphingosine-1-phosphate analog FTY720 reverses obesity but not age-induced anabolic resistance to muscle contraction - Rivas, Donato A. (Am J Physiol Cell Physiol, 2019)
Sarcopenia, the age-associated loss of skeletal muscle mass and function, is coupled with declines in physical functioning leading to subsequent higher rates of disability, frailty, morbidity, and mortality. Aging and obesity independently contribute to muscle atrophy that is assumed to be a result of the activation of mutual physiological pathways. Understanding mechanisms contributing to the induction of skeletal muscle atrophy with aging and obesity is important for determining targets that may have pivotal roles in muscle loss in these conditions. We find that aging and obesity equally induce an anabolic resistance to acute skeletal muscle contraction as observed with decreases in anabolic signaling activation after contraction. Furthermore, treatment with the sphingosine-1-phosphate analog FTY720 for 4 wk increased lean mass and strength, and the anabolic signaling response to contraction was improved in obese but not older animals. To determine the role of chronic inflammation and different fatty acids on anabolic resistance in skeletal muscle cells, we overexpressed IKKβ with and without exposure to saturated fatty acid (SFA; palmitic acid), polyunsaturated fatty acid (eicosapentaenoic acid), and monounsaturated fatty acid (oleic acid). We found that IKKβ overexpression increased inflammation markers in muscle cells, and this chronic inflammation exacerbated anabolic resistance in response to SFA. Pretreatment with FTY720 reversed the inflammatory effects of palmitic acid in the muscle cells. Taken together, these data demonstrate chronic inflammation can induce anabolic resistance, SFA aggravates these effects, and FTY720 can reverse this by decreasing ceramide accumulation in skeletal muscle.